Potential for HER-2/neu molecular targeted therapy for invasive bladder carcinoma: comparative study of immunohistochemistry and fluorescent in situ hybridization - Matsubara, Hiroyuki; Yamada, Yoshiaki; Naruse, Katsuya; Nakamura, Kogenta; Aoki, Shigeyuki; Taki, Tomohiro; Tobiume, Motoi; Zennami, Kenji; Katsuda, Remi; Honda, Nobuaki (Oncology reports, 2008)
Analysis of HER-2/neu expression in invasive bladder carcinoma was performed in order to evaluate the potential for molecular targeted therapy targeting HER-2. The subjects were 40 patients who were pathologically diagnosed with invasive transitional cell carcinoma of the bladder (pT2 to pT4). A Hercep test kit was used to detect HER-2 expression, and a Path Vysion kit was used for gene amplification. On immunohistochemical (IHC) staining, the primary tumors were HER-2 positive in 17 patients (17/40, 42.5%). According to the classification of grade, one Grade 2 patient (1/3) and 16 Grade 3 patients (16/37) were positive (P=0.99). According to the classification of stage, 12 pT2 patients (12/22, 54.5%), 2 pT3 patients (2/13, 15.3%), and 3 pT4 patients (3/5, 60%) were positive (P=0.55). Lymph node metastasis was found in 10 patients, and 3 pN2 patients were HER-2 positive (3/6, 50%) (P=0.32). A statistically significant difference was observed between HER-2-positive primary tumors and metastatic lymph nodes (P=0.02). In fluorescent in situ hybridization (FISH), HER-2/neu gene amplification was detected in the primary tumors in 5 patients (5/40, 12.5%). In all these patients, IHC staining was determined as 3+. Lymph node metastasis was found in 3 pN2 patients (3/6) (P=0.32), and in these patients with HER-2/neu gene-amplified metastatic lymph nodes, the primary tumors were also positive for gene amplification (P=0.02). In these cases, IHC staining was 3+ as well. The concordance rate of IHC-positive cases with cases positive for HER-2/neu gene amplification in FISH was 12.5% (5/40), and the concordance rate of IHC 3+ and gene amplification was 71%. This result suggests that, at present, patients who may potentially benefit from molecular targeted therapy targeting HER-2/neu for invasive bladder carcinoma should be identified by gene amplification analysis using FISH in IHC 3+ patients. In addition, it suggested that efficacy of molecular targeted therapy can be expected even for patients with metastatic lymph nodes as long as the primary tumors are positive for HER-2 expression.